Risk Factors for Experiencing Gender Based Violence Across Racial Groups - Baldwin-White, Adrienne (Journal of interpersonal violence, 2023)
BackgroundCollege student interpersonal violence victimization is a major public health issue. Sexual assault and intimate partner violence have negative effects on mental and physical health, as well as an individual’s ability to perform well academically and fully participate in the college experience. Because an individual’s race impacts how they experience the world, it is important to consider racial differences in experiences of interpersonal violence.Study QuestionThis study sought to understand the particular characteristics of Black, White, and Hispanic students that increase their risk of experiencing interpersonal violence victimization.Method and SubjectsResearchers performed a latent class analysis using the Spring 2013 data from the American College Health Association’s National College Health Assessment II to determine whether the risk factors for victimization of college students vary based on race. Data was collected from 123,078 college students attending 153 institutions of higher learning.FindingsResults of this latent class analysis showed a 5 class solution where each class had unique risks that increased the potential for interpersonal violence victimization based on the race of the respondent.ImplicationsGroup based differences need to be considered when developing prevention strategies to reduce the risk of victimization on college campuses. Because different risks increase victimization for White, Black, and Hispanic students, it is important to consider how risk reduction strategies may differ for these groups; and ensure that all prevention strategies are culturally informed.